The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/min13020232
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Palm Oil Fuel Ash (POFA) as an Admixture for the Synthesis of a Gold Mine Tailings-Based Geopolymer Composite

Abstract: The repurposing of gold (Au) mine tailings from artisanal and small-scale mining (ASGM) operations via alkali activation technology is a promising strategy for waste reduction in developing countries. Direct activation of mine tailings, however, is challenging because these materials contain relatively low aluminum (Al)-bearing minerals. In this study, palm oil fuel ash (POFA) was elucidated as a high Al-bearing waste derived-admixture for the synthesis of an ASGM tailings-based geopolymer composite. Semi-quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 63 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…Qing et al [8] produced geopolymer concrete with a compressive strength of 47.6 MPa using the alkali-hydrothermal activation of quartz powder at 300 • C. Although it meets 42.5 cement standards, high temperatures may hinder its sustainability. Orozco et al [9] developed sustainable bricks by activating gold mine tailings with NaOH or (CaOH) 2 and curing at 80 • C. Opiso et al [10] found that adding 10% palm oil fuel ash to gold mine tailings-based geopolymer bricks improved their mechanical qualities and allowed for room-temperature curing, resulting in cost and CO 2 emission savings. However, creating geopolymers with suitable mechanical characteristics using MTs as raw materials is challenging due to the large number of nonreacting phases, particularly quartz.…”
Section: Introductionmentioning
confidence: 99%
“…Qing et al [8] produced geopolymer concrete with a compressive strength of 47.6 MPa using the alkali-hydrothermal activation of quartz powder at 300 • C. Although it meets 42.5 cement standards, high temperatures may hinder its sustainability. Orozco et al [9] developed sustainable bricks by activating gold mine tailings with NaOH or (CaOH) 2 and curing at 80 • C. Opiso et al [10] found that adding 10% palm oil fuel ash to gold mine tailings-based geopolymer bricks improved their mechanical qualities and allowed for room-temperature curing, resulting in cost and CO 2 emission savings. However, creating geopolymers with suitable mechanical characteristics using MTs as raw materials is challenging due to the large number of nonreacting phases, particularly quartz.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, due to the enrichment of metal mining waste in certain chemical elements of interest, in some cases, this waste could be reused as a source of raw materials for further uses, e.g., in nanomedicine [12]. The revalorization of metal mining waste using new technologies is a promising strategy for its quantitative reduction [13], as well as for the effective recovery of some elements contained in these tailings [12]. In this sense, the goal of reusing industrial waste and moving towards waste-free production is a trend that is likely to become the norm in the medium to long term, both because of the need for mineral raw materials and the depletion of their main deposits [10,14].…”
Section: Introductionmentioning
confidence: 99%
“…The inorganic silica-alumina cementing material has a threedimensional network structure. The commonly used active silicate raw materials include fly ash [5,6], refined blast furnace slag [7] and other wastes, such as red mud, rice husk ash, and some mine tailings [8][9][10]. All kinds of geopolymers with excellent properties have been prepared.…”
Section: Introductionmentioning
confidence: 99%